2013
DOI: 10.4081/oncol.2013.e1
|View full text |Cite
|
Sign up to set email alerts
|

Tumorigenesis: cell defense against hypoxia?

Abstract: Microenvironmental elements can directly contribute to the induction and the maintenance of tumor. Oxygen is the main element in the cell microenvironment and hypoxia can affect the process of tumorigenesis. In response to hypoxia, cells change their pattern and characteristics. These changes suggest that it is not just adaptation, but some sort of cell defense against hypoxia. If hypoxia is corrected, then cell defense mechanisms are interrupted. An examination of the process of tumorigenesis helps to design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…Macrophages are highly plastic cells that can infiltrate and be educated within the TME . Hypoxia represents a key micro‐environmental stressor that governs multiple phenomena associated with tumor progression, such as immune evasion, neoangiogenesis, and metastatic dissemination . As the hallmark feature of malignant tumors, hypoxia has been demonstrated to play a crucial role in TAM infiltration in the TME .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Macrophages are highly plastic cells that can infiltrate and be educated within the TME . Hypoxia represents a key micro‐environmental stressor that governs multiple phenomena associated with tumor progression, such as immune evasion, neoangiogenesis, and metastatic dissemination . As the hallmark feature of malignant tumors, hypoxia has been demonstrated to play a crucial role in TAM infiltration in the TME .…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Hypoxia represents a key microenvironmental stressor that governs multiple phenomena associated with tumor progression, such as immune evasion, neoangiogenesis, and metastatic dissemination. 11,12 As the hallmark feature of malignant tumors, hypoxia has been demonstrated to play a crucial role in TAM infiltration in the TME. [13][14][15] Notably, not only the number of TAMs but also their phenotype regulates carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown MMP-14 was highly expressed in different tumor tissues, and its expression could promote the migration, invasion and metastasis of tumor cells in vitro and in vivo [71]. Potentially, MMP14 may play a crucial role in different biological processes of cancer and normal tissues [72].…”
Section: Discussionmentioning
confidence: 98%
“…Supporters of oxygen therapy claim that low levels of oxygen enable tumor cells to adapt and thrive. Accordingly, oxygenation of tumor cells interferes with their proteomic and genomic changes and can destroy them [ 14 , 15 ]. The initial idea of oxygen therapy for cancer treatment using ozone or hydrogen peroxide, decomposing into oxygen, dates back decades ago [ 30 – 37 ].…”
Section: Discussionmentioning
confidence: 99%